Communication Skills of a Teacher Role in the Development of the Students’ Academic Success - Dr. Vaishaliben Bhogilal Patel (Researchparks Publishing, 2021)
The current study was designed to assess students' perceptions of the role of teacher communication skills in their academic success. Researchers designed comprehensive questionnaires containing information on socioeconomic and demographic aspects of the study to achieve the stated goals. All universities offering sports science and physical education courses are considered subjects of study. Empirical data on the role of teacher communication skills in students' academic success these data were collected from respondents through personal exposure and use of a developed scale. After the data is collected, the data is finally classified in the form of a table, and the data is analyzed by regression method. After analyzing the data, the researchers concluded that teachers' communication skills play an important role in students' academic performance.